2020
DOI: 10.1177/1056789519900784
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic performance and damage simulation of fiber metal laminates under high-velocity oblique impact

Abstract: Fiber metal laminates have been successfully applied in military aircrafts, armor vehicles and other modern engineering industries as protective structures due to their outstanding impact resistant properties. Prediction of the ballistic performance and investigation on the damage mechanism of the fiber metal laminates under general oblique impact conditions still remain a very challenging issue. In this study, a nonlinear dynamic finite element model in terms of continuum damage mechanics including i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…However, the maximum damage length “secondary failures” are quite considerable for the carbon/Epoxy experimental case. Carbon/Epoxy’s relatively small main damage area may be explained by its fragile failure characteristics, since damage tends to be more localized, similarly to the expected result in a high energy ballistic test [ 18 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the maximum damage length “secondary failures” are quite considerable for the carbon/Epoxy experimental case. Carbon/Epoxy’s relatively small main damage area may be explained by its fragile failure characteristics, since damage tends to be more localized, similarly to the expected result in a high energy ballistic test [ 18 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these tests, a flat, rectangular composite coupon plate is subjected to an out-of-plane, concentrated impact load using a drop-weight device with a hemispherical impactor. The drop-weight potential energy is defined by the specified mass and drop height of the impactor [ 16 , 17 , 18 , 19 ]. Information obtained from computer models and experimental results on the coupon-scale analysis can be then used to investigate the behavior of the full-scale component ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…FMLs have the advantages of both metals and polymers such as high wear strength, impact resistance, high corrosion resistance, etc. (Asundi and Choi, 1997;Bahari-Sambran et al, 2018a, 2018bZhang et al, 2020). In this regard, Evancho (2001) has declared that the puncture resistance of glass-reinforced aluminum laminate (GLARE) is 50% higher than the aluminum alloy layer with the same thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The examination by Zhang et al [11] explored the ballistic execution of two diverse primary fibre metal laminates exposed to high-speed diagonal effect by impact by rigid hemispherical nose projectile with 0 ∘ , 30 ∘ , 45 ∘ and 60 ∘ angles. Their results showed that the projectile diverges during the oblique impact, and the deflection angle diminishes with rising impact velocity.…”
Section: Introductionmentioning
confidence: 99%